2016
DOI: 10.1007/s11764-016-0526-7
|View full text |Cite
|
Sign up to set email alerts
|

Fear of cancer recurrence in survivor and caregiver dyads: differences by sexual orientation and how dyad members influence each other

Abstract: Purpose To identify explanatory factors of fear of recurrence (FOR) in breast cancer survivors of different sexual orientations and their caregivers, and to assess the directionality in the survivor and caregiver dyads’ FOR. Methods We recruited survivors of non-metastatic breast cancer of different sexual orientations and invited their caregivers into this study. Using a telephone survey, we collected data from 167 survivor and caregiver dyads. Using simultaneous equation models and a stepwise selection pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 51 publications
1
56
2
2
Order By: Relevance
“…However, 3 studies of women with breast cancer found that SGM survivors had comparable or even better adjustment than heterosexual survivors . In addition, fear of recurrence, a commonly reported outcome among cancer survivors, was reported at lower levels among SM women than among heterosexual women with breast cancer . Another study found that resilience mediated the association between perceived discrimination and distress in SM women with breast cancer .…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…However, 3 studies of women with breast cancer found that SGM survivors had comparable or even better adjustment than heterosexual survivors . In addition, fear of recurrence, a commonly reported outcome among cancer survivors, was reported at lower levels among SM women than among heterosexual women with breast cancer . Another study found that resilience mediated the association between perceived discrimination and distress in SM women with breast cancer .…”
Section: Resultsmentioning
confidence: 88%
“…We identified 14 studies that characterized the mental health impact and degree of adjustment to cancer . In 1 large survey study of individuals with a history of cancer that compared SGM with propensity score‐adjusted heterosexual peers, SGM survivors reported higher rates of depression and relationship difficulty .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to heterosexuals, sexual minority cancer survivors and their caregivers experience (and anticipate) sexual and gender prejudice, microaggressions (i.e., commonplace social exchanges that carry disparaging messages), and discriminatory and heteronormative policies within healthcare settings [34]. With the exception of a focused line of research by one team showing that sexual minority breast cancer survivors and their caregivers had similar levels of distress [35] and interdependent fear of cancer recurrence [35,36], studies, to date, have not explicitly assessed differences in dyads' participation in breast cancer research by sexual orientation. Given the high translational significance of understanding dyad participation in breast cancer survivorship research, the overall objective of this study was to identify factors associated with successful dyad enrollment (i.e., caregiver participation) into a telephone-based study with particular attention to differences in caregiver recruitment between heterosexual and sexual minority breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Fear, worry, or concern about this uncertainty, collectively called fear of cancer recurrence (FCR), has been associated with greater depression and poorer quality of life among cancer survivors . Studies also have reported that FCR among family caregivers sometimes is higher than that of their patients . Caregivers' FCR that their patient's cancer may return or progress has been associated with their own greater anxiety, depression, and loneliness, and a poorer quality of life as well …”
Section: Introductionmentioning
confidence: 99%